Factors Influencing the Intention of Jakarta Workers to Move to the State Capital in Kalimantan: From Systematic Literature Review to Conceptual Framework of Push-Pull-Mooring - Iskandar, Yelita Anggiane (Universitas Jember, 2023)
The plan to relocate the national capital (IKN) from DKI Jakarta to Kalimantan Island will soon be realized when the population relocation is initiated by workers, one of whom is from the central ministry sector. This has never been studied before regarding the need to change residence, so the factors that encourage or restrain workers from moving to IKN have not been identified. Ideally, the transfer of these workers to IKN is based on full willingness and awareness of the conditions of life that will be lived in the future. To find out how far the intention of Jakarta workers is to move to IKN, factor analysis is needed using the Structural Equation Modeling (SEM) method. The concept used to investigate these push, pull, and restraint factors is push-pull-mooring (PPM). These three factors are important to study to obtain a model structure that can be used as a direction for IKN development. In addition, this research is also intended to find out technical information related to the reasons behind the readiness of Jakarta workers to change their domicile to IKN so that the expectations of the benefits of the new capital city can be accommodated as well as possible by interested parties, such as the central government. and regions, including the private sector.